2019
DOI: 10.1016/j.schres.2018.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Implementation intention training for prospective memory in schizophrenia: A 3-month follow-up study

Abstract: The beneficial effect of implementation intentions (II) on prospective memory (PM) deficits in patients with schizophrenia has been reported. However, these studies were limited to brief interventions such that the transfer and long-term effects of II training remains unclear. This study examined whether a 10-session II programme could improve PM performance, social functioning and functional capacity in patients with schizophrenia immediately after training and at 3-month follow-up. Patients with schizophreni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…These discrepancies between immediate and long-term efficacy might be due to a decline in performance over time. A study on implementation intention, one of the most commonly used PM training regimes, also demonstrated a similar effect (Chen et al, 2019 ); they found a significant improvement in PM at post-test, as measured by the computerised PM task (Ƞp 2 = 0.17 for EBPM and Ƞp 2 = 0.11 for TBPM) and the naturalistic PM task (i.e., phone call task; Ƞp 2 = 0.10). At the three-month follow-up, although the implementation intention group still demonstrated a significant effect in the EBPM measures and phone call task, the overall effect size in the EBPM measures dropped (i.e., Ƞp 2 from 0.17 to 0.11) and the effect size in the phone call task increased (i.e., Ƞp 2 from 0.10 to 0.11).…”
Section: Discussionmentioning
confidence: 75%
“…These discrepancies between immediate and long-term efficacy might be due to a decline in performance over time. A study on implementation intention, one of the most commonly used PM training regimes, also demonstrated a similar effect (Chen et al, 2019 ); they found a significant improvement in PM at post-test, as measured by the computerised PM task (Ƞp 2 = 0.17 for EBPM and Ƞp 2 = 0.11 for TBPM) and the naturalistic PM task (i.e., phone call task; Ƞp 2 = 0.10). At the three-month follow-up, although the implementation intention group still demonstrated a significant effect in the EBPM measures and phone call task, the overall effect size in the EBPM measures dropped (i.e., Ƞp 2 from 0.17 to 0.11) and the effect size in the phone call task increased (i.e., Ƞp 2 from 0.10 to 0.11).…”
Section: Discussionmentioning
confidence: 75%
“…The individual is asked to repeat this sequence a certain number of times (for example, when I reach the office, I will make a phone call to John). An imagery component may also follow it (for example, apart from rehearsing the 'if' and 'then' statements, imagine performing the task for 30 s) [24,25]. Implementation intention training effectively improves ProM in schizophrenia [24,25].…”
Section: Remedial Strategies For Prom Deficitsmentioning
confidence: 99%
“…An imagery component may also follow it (for example, apart from rehearsing the 'if' and 'then' statements, imagine performing the task for 30 s) [24,25]. Implementation intention training effectively improves ProM in schizophrenia [24,25]. The improvement is (a) seen even if the cognitive load of the intervening task increases, (b) sustained after the active intervention is stopped, and (c) observed both in terms of laboratorybased as well as real-life ProM tasks [24,25].…”
Section: Remedial Strategies For Prom Deficitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Switch was specifically developed to tackle all of the difficulties involved in motivation. Thus, the potential of the intervention is maximized as strategies are available across all processes (e.g., Chen et al, 2019;Farquharson & MacLeod, 2014;Favrod et al, 2019), from the premises of motivation to goal attainment and maintenance.…”
Section: Introductionmentioning
confidence: 99%